2014
DOI: 10.1103/physrevlett.113.261802
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Coherent Production ofπ±in Neutrino and Antineutrino Beams on Carbon fromEνof 1.5 to 20 Ge

Abstract: Neutrino-induced coherent charged pion production on nuclei νμA→μ(±)π(∓)A is a rare, inelastic interaction in which a small squared four-momentum |t| is transferred to the recoil nucleus, leaving it intact in the reaction. In the scintillator tracker of MINERvA, we remove events with evidence of particles from nuclear breakup and reconstruct |t| from the final-state pion and muon. We select low |t| events to isolate a sample rich in coherent candidates. By selecting low |t| events, we produce a model-independe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 63 publications
(96 reference statements)
9
71
2
1
Order By: Relevance
“…The cross sections are measured as a function of the pion energy, pion angle, and Q 2 , which characterize the coherent pion production kinematics. A subset of these results based on these same data was published earlier [1]. The results presented in this paper have a revised treatment of backgrounds, additional differential distributions, a new prediction of the neutrino and antineutrino fluxes in the beam and the correlations between the neutrino and antineutrino measurements.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The cross sections are measured as a function of the pion energy, pion angle, and Q 2 , which characterize the coherent pion production kinematics. A subset of these results based on these same data was published earlier [1]. The results presented in this paper have a revised treatment of backgrounds, additional differential distributions, a new prediction of the neutrino and antineutrino fluxes in the beam and the correlations between the neutrino and antineutrino measurements.…”
Section: Introductionmentioning
confidence: 79%
“…Rates for interactions where there are no applicable measurements were taken from the hadron interaction model used in the simulation (FTFP-BERT). 1 Predictions from the weighted model were compared against in situ measurements of neutrino scattering events with low hadronic recoil to validate the model. An in situ measurement [41] of ν þ e − → e − þ ν provided an additional constraint on the flux, giving a roughly 2%-4% reduction in the flux prediction and an ∼1% reduction in the flux uncertainty.…”
Section: Neutrino Beam and Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of |t|, from directly measured kinematic variables of the muon and pion, allowed a model-independent measurement of the coherent differential cross section [8]. The model to which the data were compared to (Rein-Sehgal [8]), poorly reproduced the measured kinematics ( fig.…”
Section: Coherent Pionmentioning
confidence: 99%
“…Thanks to its fine grained resolution ArgoNeuT is able to perform measurements of exclusive cross-section topologies as well as observe clear indications of nuclear interactions in the argon nucleus affecting the topologies and parti- The measurement of the coherent pion production recently performed by ArgoNeuT [17] has shown that even a prototype LArTPC can compete with other detector technologies that have recently looked at this channel [18,19]. ArgoNeuT, due to its small size which prevented the containment of pions and therefore the efficient use of variables such as Q 2 and |t|, used a boosted decision tree to select candidate events based on the combined values of several kinematic variables, including the opening angle and presence of additional activity near the vertex.…”
Section: Argoneut Exclusive Cross-section and Lartpc-enabled Physics mentioning
confidence: 99%